The guiding value of hybrid resting full-cycle ratio and fractional flow reserve strategy for percutaneous coronary intervention in a Chinese real-world cohort with non-ST elevation acute coronary syndrome - Lei, Yumeng; Zhang, Shuaiyong; Li, Mengyao; Wang, Jiawang; Wang, Yunfei; Zhao, Lei; Yan, Wei; Chen, Ming; Su, Yanjie; Yu, Jing; Yu, Na; Dong, Tongjun; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective: The study aimed to assess the correlation and agreement between resting full-cycle ratio (RFR) and fractional flow reserve (FFR), and evaluate the guiding value of a hybrid RFR-FFR strategy for percutaneous coronary intervention (PCI) in a Chinese real-world cohort with non-ST elevation acute coronary syndrome (NSTE-ACS). Methods: A total of 109 NSTE-ACS patients (149 diseased vessels), who underwent an invasive physiological assessment in Cangzhou Central Hospital, Hebei Medical University, were prospectively enrolled from September 2021 to May 2022. FFR ≤0.80 was used as the gold standard for coronary artery functional ischemia. We utilized the Pearson correlation and Bland-Altman analysis to assess the correlation and agreement between RFR and FFR. The diagnostic value of RFR predicting FFR ≤ 0.80 was evaluated in accordance with the receiver operating characteristic (ROC) curve. The hybrid RFR-FFR strategy, which was established according to determining the “grey zone” of RFR (FFR was further assessed using vasodilators only for diseased vessels in the “grey zone”), needed to afford over 95% global agreement with the FFR-only strategy. Results: RFR was significantly linearly linked with FFR (R2 = 0.636, P <0.001). The accuracy, specificity, and sensitivity for RFR ≤0.89 predicting FFR ≤0.80 were 81.2%, 70.8%, and 86.1%, respectively. The area under the ROC curve for RFR predicting FFR ≤0.80 was 0.881 (P <0.001), and the cutoff value was 0.90. The “grey zone” of RFR was 0.85-0.93. The positive and negative predictive values of the hybrid RFR-FFR strategy were 0.95 and 0.93, respectively. The hybrid RFR-FFR strategy exhibited an agreement of 96.0% with FFR and obviated the need for a vasodilator by 60.4%. Conclusions: RFR and FFR have high correlation and consistency. The hybrid RFR-FFR strategy highlights considerably enhanced agreement with the FFR-only strategy, whilst making the requirement of vasodilator administration less than a half.